2020
DOI: 10.1111/jphp.13267
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological screening of fenofibrate-loaded solid dispersion in fructose-induced diabetic rat

Abstract: Objectives Hyperlipidaemia is a common phenomenon in diabetes mellitus. Fenofibrate (FF) is a good candidate for the treatment of lipid abnormalities in patients with type 2 diabetes. But the bioavailability as well as therapeutic efficacy of this drug is limited to its dissolution behaviour. Here, the authors assess the therapeutic efficacy of a newly formulated solid dispersion of fenofibrate (SDF) having enhanced dissolution profiles in contrast to pure FF using fructose-induced diabetic rat model. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…In the acetic acid-induced writhing test PSD10 showed a significant decrease in the number of writhing by 1.44-fold greater compared to pure PCM at an equal dose (30 mg/kg). This result indicated that fast dissolution and subsequent rapid absorption of PCM occurred in GIT from the solid dispersion formulation (PSD10) as previously reported by various authors [43] [44] [45].…”
Section: Discussionsupporting
confidence: 84%
“…In the acetic acid-induced writhing test PSD10 showed a significant decrease in the number of writhing by 1.44-fold greater compared to pure PCM at an equal dose (30 mg/kg). This result indicated that fast dissolution and subsequent rapid absorption of PCM occurred in GIT from the solid dispersion formulation (PSD10) as previously reported by various authors [43] [44] [45].…”
Section: Discussionsupporting
confidence: 84%
“…[2] Fenofibrate (FENO) is a peroxisome proliferator-activated-α (PPAR α) receptor agonist used as a hypolipidemic drug, effective in the management of various forms of dyslipidemia. [3,4,5] As a PPAR α, it regulates gene/protein interactions which are associated in various pathological processes like regulation of β-oxidation of fatty acids, oxidative stress, inflammation and even cancer progression and tumorigenesis. [6] As a result of PPAR α activation of gene transcription and translation which leads to peroxisomes filled with hydrogen peroxide, reactive oxygen species and hydroxyl radicals act as participant in lipolysis.…”
Section: Introductionmentioning
confidence: 99%